Outcomes with General Anesthesia Compared to Conscious Sedation for Endovascular Treatment of Medium Vessel Occlusions: Results of an International Multicentric Study - Radu, Răzvan Alexandru; Costalat, Vincent; Romoli, Michele; Musmar, Basel; Siegler, James E.; Ghozy, Sherief; Khalife, Jane; Salim, Hamza; Shaikh, Hamza; Adeeb, Nimer; Cuellar-Saenz, Hugo H.; Thomas, Ajith J.; et al. (Clinical neuroradiology, 2024)
Optimal anesthetic strategy for the endovascular treatment of stroke is still under debate. Despite scarce data concerning anesthetic management for medium and distal vessel occlusions (MeVOs) some centers empirically support a general anesthesia (GA) strategy in these patients.
Online veröffentlicht: 30. April 2024
Gesehen am 21.02.2025